Cyclic γ-Peptides With Transmembrane Water Channel Properties - Chen, Jie; Li, Qiang; Wu, Pengchao; Liu, Juan; Wang, Dan; Yuan, Xiaohong; Zheng, Renlin; Sun, Rongqin; Li, Liangchun (Frontiers in Chemistry, 2020)
Self-assembling peptides can be used to design new materials for medical and biological applications. Here we synthesized and characterized two novel cyclic γ-peptides (γ-CPs) with hydrophobic inner surfaces. The NMR and FT-IR studies confirmed that the CPs could self-assemble into parallel stacking structures via intermolecular H-bonds and π-π interactions. The morphologies of the self-assembly CPs showed bundles of nanotubes via transmission electron microscopy (TEM); these nanotubes form water channels to transport water across the lipid membrane. The properties of blocking the transport of protons like natural water channels showed that the hydrophobic inner surfaces are important in artificial transmembrane water channel designs. These studies also showed that water transport was a function of pore size and length of the assemblies.